Engaging Actors for Integrating Health Policy and Systems Research into Policy Making: Case Study from Haryana State in India - Prinja, Shankar; Gupta, Rakesh; Sharma, Atul; Dalpath, Suresh Kumar; Phogat, Amit (Indian Journal of Community Health, 2017)
Background & objective: Good examples of evidence generation using Health Policy and Systems Research (HPSR) in low and middle income countries (LMIC); and its application in policy making are scarce. In this paper, we describe the experience of establishing a system of HPSR from the Haryana state in India, outline how the HPSR is being utilized for policy making and programmatic decision making, and analyse the key factors which have been critical to the implementation and uptake of HPSR. Methods: Multiple methods are employed in this case study, ranging from unstructured in-depth interviews, review of the program and policy documents, and participatory notes from the meetings. The steps towards creation of a knowledge partnership between stakeholders are outlined. Four case studies i.e. development of a plan for universal health care (UHC), nutrition policy, centralized drug procurement system and use of RAPID appraisal method highlight the use of research evidence in agenda setting, policy formulation and policy implementation respectively. Results: Our analysis shows that the most important factor which contributed to Haryana model of HPSR was the presence of a dedicated and motivated team in National Rural Health Mission (NRHM) at state level, many of whom were researchers by previous training. Overall, we conclude by highlighting the need for establishing an institutional mechanism at Central and State level where health service administrators and managers, academicians and researchers working in the field of health system from medical colleges, public health schools, management and technology institutions and social science universities can identify health system research priorities. Increased budgetary allocation for HPSR is required.